A history of law in Canada. - Girard, Philip; Phillips, Jim, 1954-; Brown, R. Blake (published for The Osgoode Society for Canadian Legal History by University of Toronto Press, 2018)
"A History of Law in Canada is an important three-volume project. Volume One begins at a time just prior to European contact and continues to the 1860s, Volume Two covers the half century after Confederation, and Volume Three covers the period from the beginning of the First World War to 1982, with a postscript taking the account to approximately 2000. The history of law includes substantive law, legal institutions, legal actors, and legal culture. The authors assume that since 1500 there have been three legal systems in Canada -- the Indigenous, the French, and the English. At all times, these systems have co-existed and interacted, with the relative power and influence of each being more or less dominant in different periods. The history of law cannot be treated in isolation, and this book examines law as a dynamic process, shaped by and affecting other histories over the long term. The law guided and was guided by economic developments, was influenced and moulded by the nature and trajectory of political ideas and institutions, and variously exacerbated or mediated intercultural exchange and conflict. These themes are apparent in this examination, and through most areas of law including land settlement and tenure, and family, commercial, constitutional, and criminal law"-- Provided by publisher.
Keywords: Law -- Canada -- History.; Droit -- Canada -- Histoire.; LAW -- Essays.; LAW -- General Practice.; LAW -- Jurisprudence.; LAW -- Paralegals & Paralegalism.; LAW -- Practical Guides.; LAW -- Reference.; HISTORY -- Canada -- Pre-Confederation (to 1867); Law; Canada; Electronic books.; History